Biodiesel production from edible oils using algal biochar/CaO/K2CO3 as a heterogeneous and recyclable catalyst. (May 2021) - Foroutan, Rauf; Mohammadi, Reza; Razeghi, Jafar; Ramavandi, Bahman
Abstract: A new heterogeneous biochar/CaO/K2 CO3 catalyst was fabricated to produce biodiesel from waste edible oil. In this catalyst, the biochar was produced from brown algae of Sargassum oligocystum and CaO from eggshells. The XRD result showed that the biochar, CaO, and synthesized catalyst have a crystalline structure. Response surface methodology-central composite design (RSM-CCD) and artificial neural network (ANN) methods were used to investigate the effect of parameters and determine optimal conditions. Also, the maximum efficiency of biodiesel production (98.83%) was predicted by the RSM-CCD method at 65 °C, 4 wt% catalyst content, 200 min duration, and 18: 1 methanol to oil ratio. The process of biodiesel production was exothermic. The activation energy and frequency factor were calculated 45.53 kJ/mol and 6.03 × 10 +4 min −1, respectively. Biodiesel properties were evaluated according to international standards (ASTM D6751 and EN14214 ). The catalyst was reused for up to 90% efficiency in up to 5 steps. Graphical abstract: Image 1 Highlights: The biochar/CaO/K2 CO3 catalyst was fabricated from algal biochar and eggshell CaO. The catalyst was used to biodiesel production from edible waste oil successfully. Catalyst properties were characterized using XRD, SEM, BET, FTIR TGA, and AFM. RSM and ANN were used to optimize the variables of the biodiesel production. Biodiesel fulfil most significant European EN14214 standard properties.